HUBUNGAN SUMBER INFORMASI DAN POLA ASUH IBU DENGAN PENGETAHUAN PERSONAL HYGIENE SAAT MENSTRUASI PADA REMAJA DI SMAS MARTIA BHAKTI TAHUN 2020 - Adies Ariyani, (2021)
The importance of providing information and the role of parents to adolescents are impacting to the knowledge of adolescents themselves. Adolescent girls who experience greater menstruation have an impact on exposure to several diseases such as vulva hygiene and cervical cancer, besides that it will interfere with organ function if they cannot maintain the cleanliness of their reproductive organs. The research objective was to determine the relationship between information sources and parenting styles with knowledge of personal hygiene during menstruation in adolescents. This research used quantitative method with cross-sectional design and uses purposive sampling technique. The number of samples was 85 teenage students of Martia Bhakti Bekasi High School. Measuring tool for this research is questionnaire which is distributed online to respondents. Data analysis used the chi-square test. The results of this study showed that there was a significant relationship between information source variables and personal hygiene knowledge variables during menstruation in adolescents (p = 0,002), there was a significant relationship between maternal parenting variables and personal hygiene knowledge during menstruation in adolescents (p = 0,000). Teenagers are advised to lokk for more varied sources of information such as health workers and so that, they can balance the source information between parenting style they obtained and valid information.